C-REACTIVE PROTEIN: AN AID FOR DIAGNOSIS OF ACUTE APPENDICITIS - Ahmed, Nauman (Journal of Ayub Medical College Abbottabad, 2017)
Background: Delayed or wrong diagnosis of acute appendicitis in patients results in complications like perforation, gangrene, etc. which carries a significant amount of morbidity and mortality to the patients. Thus, timely diagnosis of acute appendicitis is crucial to prevent these complications. Recently, it was found that serum C-reactive protein (CRP) individually can be a useful marker, thus in resource limited settings (i.e., access to ultrasonography) simple laboratory investigation can be of extreme utility for the diagnosis of acute appendicitis. Current study aimed to ascertain and determine the role of C Reactive Protein (CRP) as a complementary test to decrease the rate of negative appendectomies in tertiary care hospitals of Pakistan. Methods: Using non-probability consecutive sampling, 112 patients with the initial diagnosis of acute appendicitis on history and clinical examination were enrolled. A blood sample was taken for serum level of CRP. Results: Mean age was 20.8±8.6 years and 51 (45.5 %) patients were males. Pathologic review revealed 100 cases (89.3%) of acute appendicitis, 4 patients (3.6%) had perforated appendix while 8 patients (7.1%) had normal appendix. Sensitivity, specificity, positive and negative predictive value and diagnostic accuracy of C reactive protein >24 mg/lit taking histology as gold standard came out 25.9%, 100%, 100%, 9.4% and 31.25% respectively. Conclusion: It was concluded that CRP >48 mg/lit is an indication of perforated appendix and when the surgeon is in fix whether to go conservatively or apply some intervention, CRP can be a good diagnostic aid Keywords: Acute appendicitis; C Reactive Protein; Diagnostic accuracy; Perforated appendix